Magneto-inductive networked rescue system (MINERS): taking sensor networks underground. - Markham, A; Trigoni, N (ACM, 2012)
Wireless underground networks are an emerging technology which have application in a number of scenarios. For example, in a mining disaster, flooding or a collapse can isolate portions of underground tunnels, severing wired communication links and preventing radio communication. In this paper, we explore the use of low frequency magnetic fields for communication, and present a new hardware platform that features triaxial transmitter/receiver antenna loops. We point out that the fundamental problem of the magnetic channel is the limited bitrate at long ranges, due to the extreme path loss of 60 dB/decade. To this end, we present two complementary techniques to address this limitation. Firstly, we demonstrate magnetic vector modulation, a technique which modulates the three dimensional orientation of the magnetic vector. This increases the gross bitrate by a factor of over 2.5, without an increase in transmission power or bandwidth. Secondly, we show how in a multi-hop network latencies can be dramatically reduced by receiving multiple parallel streams of frequency multiplexed data in a many-to-one configuration. These techniques are demonstrated on a working hardware platform, which for flexible operation, features a software defined magnetic transceiver. Typical communication range is approximately 30 m through rock. © 2012 ACM.